EVALUASI PENGGUNAAN OBAT SUSUNAN SARAF PUSAT (SSP) PADA PASIEN GERIATRI BERDASARKAN KRITERIA BEERS : Evaluation of Central Nervous System (CNS) Medication Use in Geriatric Patients Based on the Beers Criteria - Rizki Nurul Azizah; -, Erna Prasetya Ningrum (CENDEKIA EKSAKTA, 2025)
Geriatric patients are highly vulnerable to the use of Potentially Inappropriate Medications (PIMs) due to age-related physiological changes in pharmacokinetics and pharmacodynamics that may affect the body’s ability to process medications. Therefore, evaluation of medication use is essential to determine the safety of drugs administered to geriatric patients. This study aimed to describe the characteristics of geriatric patients receiving central nervous system (CNS) medications based on sex and disease profiles at the inpatient unit of RSUD Tugurejo Semarang from January to December 2022, to assess the patterns of CNS drug use in geriatric inpatients during the same period, and to evaluate the appropriateness of CNS medication use in geriatric patients in terms of drug appropriateness and patient appropriateness based on the 2023 Beers Criteria. This study employed a descriptive design with retrospective data collection, and purposive sampling was used as the sampling technique. The study subjects were geriatric inpatients who received CNS medications at RSUD Tugurejo Semarang from January to December 2022. The study sample consisted of hospitalized geriatric patients aged ≥65 years. The results showed that male patients accounted for 56% of the total 41 geriatric patients included in the study. The most common age group among geriatric patients receiving CNS medications was 65–69 years, accounting for 59%. The most frequently used CNS medication classified as “to be avoided” in geriatric patients was alprazolam (37%), while CNS medications with disease interactions were most commonly represented by donepezil, with three cases (100%). Evaluation of medication appropriateness revealed 45 cases (67%) of appropriate drug use and 63 cases (94%) of appropriate patient use.